Extracellular vesicles in hematological malignancies: EV-dence for reshaping the tumoral microenvironment - Van Morckhoven, David; Dubois, Nathan; Bron, Dominique; Meuleman, Nathalie; Lagneaux, Laurence; Stamatopoulos, Basile (Frontiers in Immunology, 2023)
Following their discovery at the end of the 20th century, extracellular vesicles (EVs) ranging from 50-1,000 nm have proven to be paramount in the progression of many cancers, including hematological malignancies. EVs are a heterogeneous group of cell-derived membranous structures that include small EVs (commonly called exosome) and large EVs (microparticles). They have been demonstrated to participate in multiple physiological and pathological processes by allowing exchange of biological material (including among other proteins, DNA and RNA) between cells. They are therefore a crucial way of intercellular communication. In this context, malignant cells can release these extracellular vesicles that can influence their microenvironment, induce the formation of a tumorigenic niche, and prepare and establish distant niches facilitating metastasis significantly impacting the phenotypes of surrounding cells and turning them toward supportive roles. In addition, EVs are also able to manipulate immune response and to establish an immunosuppressive microenvironment. This in turn allows for ideal conditions for heightened chemoresistance and increased disease burden. Here, we review the latest findings and reports studying the effects and therapeutic potential of extracellular vesicles in various hematological malignancies. The study of extracellular vesicles remains in its infancy; however, rapid advances in the analysis of these vesicles in the context of disease allow us to envision prospects to improve the detection and treatment of hematological malignancies.